Investigation of single nucleotide polymorphisms of human vitamin D receptor gene and their subsequent effects on the receptor structure and function by in silico methods - Das, Mitali; Biswas, Rajkrishna; Sengupta, Mrinmoyee (International Journal of Research in Medical Sciences, 2025)
Background: Vitamin D receptor (VDR) polymorphism play vital role in genetic regulation of bone mass. It has been identified that the occurrence of osteoporosis mainly caused by mutations in functional regions of the VDR gene which can be highly disturb the metabolism of minerals especially the calcium ions. Our goal in this study is to use in silico methodologies and publicly accessible web databases to evaluate the impact of missense SNPs in the human VDR gene. Methods: We used SIFT, VEP, PROVEAN, SNPs & GO, and PANTHER to predict the functional effects of mutations. I-Mutant 2.0 and Project HOPE were used to estimate the impacts on the protein’s stability and three-dimensional structure. GeneMANIA has been used to evaluate how VDR gene would interact with 20 other genes. Results: We estimate the effects of an amino acid substitution on protein structure and function depending on sequence homology, physical properties of amino acids and comparative physical properties respectively and also predicts the possible effect of an amino acid substitution on protein activity. Conclusions: Overall, this is a thorough study that gives a quick overview of all the information on the clinically important missense SNPs of VDR gene.